2021
DOI: 10.1007/s11676-021-01308-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ontogenetic stage and leaf age on leaf functional traits and the relationships between traits in Pinus koraiensis

Abstract: Investigating the effects of ontogenetic stage and leaf age on leaf traits is important for understanding the utilization and distribution of resources in the process of plant growth. However, few studies have been conducted to show how traits and trait-trait relationships change across a range of ontogenetic stage and leaf age for evergreen coniferous species. We divided 67 Pinus koraiensis Sieb. et Zucc. of various sizes (0.3–100 cm diameter at breast height, DBH) into four ontogenetic stages, i.e., young tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 100 publications
0
7
0
1
Order By: Relevance
“…Photosynthetic rates of fully expanded leaves generally show a decline with increasing leaf age due to the reallocation of resources to young leaves to optimize the overall systemic photosynthetic returns of an individual plant, rather than resulting from leaf functional degradation (Field and Mooney, 1983;Hikosaka et al, 1994). Moreover, the photosynthetic capacity of young leaves has been shown to be significantly lower than mature leaves (Hikosaka and Shigeno, 2009;Liu et al, 2020;Ji et al, 2021). Although leaf functional traits have been regarded as important references for understanding plant ecological and growth strategies (Westoby et al, 2000(Westoby et al, , 2002, there are trade-offs among different leaf functional traits (e.g., lamina area, LMA) under the limitation of resources.…”
Section: Variations In Leaf Functional Traits Across Leaf-age Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Photosynthetic rates of fully expanded leaves generally show a decline with increasing leaf age due to the reallocation of resources to young leaves to optimize the overall systemic photosynthetic returns of an individual plant, rather than resulting from leaf functional degradation (Field and Mooney, 1983;Hikosaka et al, 1994). Moreover, the photosynthetic capacity of young leaves has been shown to be significantly lower than mature leaves (Hikosaka and Shigeno, 2009;Liu et al, 2020;Ji et al, 2021). Although leaf functional traits have been regarded as important references for understanding plant ecological and growth strategies (Westoby et al, 2000(Westoby et al, , 2002, there are trade-offs among different leaf functional traits (e.g., lamina area, LMA) under the limitation of resources.…”
Section: Variations In Leaf Functional Traits Across Leaf-age Groupsmentioning
confidence: 99%
“…Mediavilla et al (2014) contended that the interspecific differences in leaf longevity, morphology, and chemical composition of mature leaves are more notable compared to immature leaves. Ji et al (2021) report that LMA and leaf dry matter content increase significantly during the development of leaves. In addition, previous studies have shown that leaf age is closely associated with photosynthetic capacity (Field and Mooney, 1983;Han et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While more nutrient-rich, early-season leaves increase the growth rates of caterpillars [16,39], they have been found to particularly favor smaller herbivore species [4,40]. A decrease in content by leaf age has also been shown for other nutrients, such as magnesium (Mg), phosphorus (P), and potassium (K) [38,41,42] (but see opposing results for Ca [43]). N, P, K, Mg, and Ca are all essential nutrients for herbivorous insects [35,44], and micronutrients, such as Mg, have been shown to modify caterpillar species composition [45] and amplify the effect of macronutrients (N, P, K) on arthropod abundance [46].…”
Section: Introductionmentioning
confidence: 99%
“…©植物生态学报 Chinese Journal of Plant Ecology www.plant-ecology.com (Li et al, 2015;Griffith et al, 2016) (Funk et al, 2021), 但是单位质量氮的增加会使得气孔导 度增加, 从而丧失水分, 这可能是一、二级小叶的 LNC较小的原因 (Schulze et al, 1994)。 LPC整体随小 叶着生位置级别由小到大呈增大趋势(图2F), 与 LNC呈相反趋势, 这与前人LNC和LPC正相关的研 究结果 (Osnas et al, 2013;Guo et al, 2020;Ji et al, 2021) Griffith et al, 2016)。LT与LDMC在复叶 内部表现为同速生长关系(图4B), 由此推测对于外 界环境的响应二者同等程度改变, 叶片在增加其对 LT的投资时也使得LDMC增大, 这可能是LT增加, 叶肉组织增加, 叶片内空气含量降低导致的结果 (Poorter et al, 2019)。 SLA与LDMC显著负相关(图3), 这与先前一些 研究结果 (Wilson et al, 1999;Díaz et al, 2016;Anderegg et al, 2021)…”
unclassified